Definition and assessment of physical literacy in children and adolescents: a literature review - DanDan Ke (Journal of Physical Fitness and Sports Medicine, 2022)
Physical literacy has been gaining popularity worldwide in physical education, physical activity, and sports. However, more attention has been focused on the concept of physical literacy, and its assessment is still in its early stages. The primary aim of this paper is to summarize the current development of the definition, especially the assessment of physical literacy worldwide, and to provide valuable information for researchers and related policymakers in the field of physical education and sports promotion in Japan. In this review, a search of the literature in English was conducted using two major electronic databases, which yielded 38 articles that met the inclusion and exclusion criteria. This study summarized the characteristics of physical literacy definitions and assessments involved in 38 studies and then compared the similarities and differences between these assessment tools in terms of components, usage scenarios, and applicable populations. Finally, we integrated the results with the Japanese social context to provide suggestions on how to develop physical literacy in Japan.